Biomimetic hydrogel with tunable mechanical properties for vitreous substitutes. (1st October 2016) - Santhanam, Sruthi; Liang, Jue; Struckhoff, Jessica; Hamilton, Paul D.; Ravi, Nathan
Graphical abstract: Abstract: The vitreous humor of the eye is a biological hydrogel principally composed of collagen fibers interspersed with hyaluronic acid. Certain pathological conditions necessitate its removal and replacement. Current substitutes, like silicone oils and perfluorocarbons, are not biomimetic and have known complications. In this study, we have developed an in situ forming two-component biomimetic hydrogel with tunable mechanical and osmotic properties. The components are gellan, an analogue of collagen, and poly(methacrylamide-co-methacrylate), an analogue of hyaluronic acid; both endowed with thiol side groups. We used response surface methodology to consider seventeen possible hydrogels to determine how each component affects the optical, mechanical, sol-gel transition temperature and swelling properties. The optical and physical properties of the hydrogels were similar to vitreous. The shear storage moduli ranged from 3 to 358 Pa at 1 Hz and sol-gel transition temperatures from 35.5 to 43 °C. The hydrogel had the ability to remain swollen without degradation for four weeks in vitro . Three hydrogels were tested for biocompatibility on primary porcine retinal pigment epithelial cells, human retinal pigment epithelial cells, and fibroblast (3T3/NIH) cells, by electric cell-substrate impedance sensing system. The two-component hydrogels allowed for the tuning and optimizing of mechanical, swelling, and transition temperature to obtain three biocompatible hydrogels with properties similar to the vitreous. Future studies include testing of the optimized hydrogels in animal models for use as a long-term substitute, whose preliminary results are mentioned. Statement of Significance: Although hydrogels are researched as long-term vitreous substitute, none have advanced sufficiently to reach clinical application. Our work focuses on the development of a novel two component in situ forming hydrogel that bio-mimic the natural vitreous. Our thiol-containing copolymers can be injected as an aqueous solution into the vitreous cavity wherein, at physiological temperature, the rigid component will instantaneously form a physical gel imbedding the random coil copolymer. Upon subsequent oxidation, the two components will form disulfide cross-links and a stable reversible hydrogel capable of providing osmotic pressure to reattach the retina. It may be left in the eye permanently or easily removed by injection of a simple reducing agent to cleave the disulfide bonds, rather than surgery. This contribution is significant because it is expected to provide patients with a much better quality of life by improving surgical outcomes, creating much less post-operative burden, and reducing the need for secondary surgeries.